How 'best fit' excludes international graduates from employment in Australia: a Bourdeusian perspective. Issue 5 (4th July 2019) - Blackmore, Jill; Rahimi, Mark
ABSTRACT: Very few organisations, even local firms, are insulated from global economic activity or the social and cultural consequences of widespread global migration programs such as international education. Nonetheless, established recruitment processes remain stubbornly local, privileging candidates who conform to the criterion of 'people like us' to produce a 'good fit' in relation to the existing workforce. In a three-year study investigating the employment outcomes of international students graduating from Australian universities in nursing, engineering and accounting, we interviewed potential employers (multinational, medium and small) regarding their recruitment practices. We found employers considered the credential indicated technical competence while the apparently objective criteria like visa eligibility and English language ability (linguistic capital) often filtered out many international student candidates. Additionally, in the context of rising credentialism, employers additionally looked for dispositions of employability or 21 st century 'soft skills' considered to be transferrable from education into work. But the final form of distinction between applicants was based on whether the applicant would 'fit in' to the organisational culture and existing teams. Despite employers agreeing with management discourses extolling the benefits of workforce diversity with regard to gender, cultural and linguistic capitals, recruitment practices saw unconscious bias exercised against international graduates, thus reproducing monocultural rather than inclusive organisations.